2013
DOI: 10.1039/c3dt51471d
|View full text |Cite
|
Sign up to set email alerts
|

Programming MOFs for water sorption: amino-functionalized MIL-125 and UiO-66 for heat transformation and heat storage applications

Abstract: Sorption-based heat transformation and storage appliances are very promising for utilizing solar heat and waste heat in cooling or heating applications. The economic and ecological efficiency of sorption-based heat transformation depends on the availability of suitable hydrophilic and hydrothermally stable sorption materials. We investigated the feasibility of using the metal-organic frameworks UiO-66(Zr), UiO-67(Zr), H2N-UiO-66(Zr) and H2N-MIL-125(Ti) as sorption materials in heat transformations by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
196
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(214 citation statements)
references
References 56 publications
(90 reference statements)
13
196
0
Order By: Relevance
“…Water is the working fluid of choice because of its high evaporation enthalpy (2440 kJ·kg -1 at 25 °C) and non-toxicity despite the need to wor k under vacuum because of the low vapor pressure of only 3.17 kPa at 25 °C [15,25,26].…”
Section: Figurementioning
confidence: 99%
“…Water is the working fluid of choice because of its high evaporation enthalpy (2440 kJ·kg -1 at 25 °C) and non-toxicity despite the need to wor k under vacuum because of the low vapor pressure of only 3.17 kPa at 25 °C [15,25,26].…”
Section: Figurementioning
confidence: 99%
“…In recent years, metalorganic frameworks and porous carbons came into focus as potential water sorbents. [11][12][13][14][15] Besides initial experiments by Banerjee and co-workers, [16][17][18] COFs have not been investigated as potential water sorbents in detail so far. COFs have garnered significant attention owing to their tunable pore sizes and high porosity combined with their long-range ordered crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…NH 2 -MIL-125(Ti) was selected as host material because (i) the overall MOF structure is stable in aqueous media, 43,44 (ii) the multinuclear Ti-centers are both photo-and redox-active 24,45 and (iii) recent experimental 37 and theoretical studies 46 have shown that the photochemical properties can be tuned by changing the aromatic linker. It is noteworthy that NH 2 -MIL-125(Ti) has been used for photocatalytic hydrogen production, both in the absence and presence of Pt-nanoparticles, 24 suggesting that the reduction potential of the excited states in the MOF is sufficient to drive proton reduction in line with computational predictions.…”
Section: Modular Designmentioning
confidence: 99%